STUDY OF HYPOGLYCAEMIA IN LATE PRE TERM NEONATES OF NICU AND PNC OF A RURAL AREA - SINGH, KUSHAGRA; MESHRAM, REWAT (International Journal of Psychosocial Rehabilitation, 2020)
The "late preterm"are defined as births between 34 weeks 1- 6 days and 36 weeks plus 6 daysof gestational age, post last menstrual periodAt first appearance, late preterm infants have similarity to term infants in terms of Apgar scores,size, and weight.However, the care of these infants can be complex. They are often placed in well-infant nurseries under the same protocols as term infants and discharged before an adequate observation period.To study blood glucose levels in late preterm newborns admitted in NICU.To study incidence of hypoglycemia in late preterm newborns admitted in NICU. To study immediate outcome of hypoglycemic late preterm newborns.The study will be conducted in Neonatal Intensive Care Unit of JNMC and AVBRH, Sawangi (Meghe), Wardha.2 years, August 2018 to July 2020.-75Prospective Observational studyAll the late preterm newborns admitted in NICU.Infants of diabetic mother The late preterm with births between 34 weeks plus 1-7 days and 36 weeks plus 6 days of gestation calculated post last menstrual period admitted in the NICU will be included in the study. These neonates will be taken up for collecting blood sample at admission. Samples will be collected by heel prick (capillary blood) method. The glucose level will be measured using glucometer available in the NICU at 0-2, 4-6, 12,24, 48 and 72 hours of life. Those who found hypoglycemic by glucometer method will be confirmed by Glucose oxidase method in the central laboratory